The Evaluation of Character Education Strengthening Program Based on Kemataraman Culture at Elementary School in Kulon Progo Regency - Wardhani, Ratri Shinta; Wiyanto, wiyanto; Hartono, Hartono (Journal of Primary Education, 2021)
Kulon Progo is one of the regencies in the Special Region of Yogyakarta which has a Regional Regulation Number 65 of 2017 concerning Guidelines for the Implementation of Character Education Strengthening. The extracurricular culture of Kemataraman is one of the supporting activities for character development. The purpose of this study is to obtain a description of the planning, preparation, implementation, and achievements of the Kemataraman culture-based program. The research was conducted using a qualitative method with a program evaluation approach. The evaluation used CIPP model (Context, Input, Procces, Product) which is more comprehensive and effective to improve the program. Data were collected using in-depth interviews, document studies, and structured observation. The subject in this study were the Head of Education Office, the Head of Education Planning Section, Principals, class teachers, and art assistant teachers. The data analysis used Milles & Huberman analysis. The result of the study indicate that the objectives of the character education program based on Kemataraman culture have not been fully achieved. There is still gap between the forms of support by the government to schools as organizers and teachers as implementers. The researcher recommends the character education program based on Kemataraman culture at the Kulon Progo regency Elementary School to be continued with improvements.